Leaf temperature effects on gas exchange in Quercus ilex L. growing under field conditions - Gratani, Loretta (Plant Biosystems - An International Journal Dealing with all Aspects of Plant Biology, 2000)
ABSTRACT Gas exchange temperature dependence in Quercus ilex shrubs growing in the Mediterranean maquis was analysed. The gas exchange trend was monitored during the year: photosynthetic activity (A net) reached the highest average rates in early spring and autumn (12.5 µmol m-2s-1 was the absolute maximum A net measured) and the lowest rates were monitored in the middle of June. There was a good correlation (r = 0.72) between A net and g s (A net = 4.1246 ln g s + 4316; P < 0.01), indicating that stomatal control of CO2 diffusion plays an important role in controlling photosynthetic activity. Leaf temperature allowing the highest photosynthetic and stomatal conductance rates of Quercus ilex were in the range 17.5 ? 29°C. A net and gs dropped below half its maximum value when leaf temperatures were below 11.5°C and above 35.7°C. Transpiration rates (E) were strongly related to leaf temperature; E increased as leaf temperature increased and the highest E rates were monitored in June, despite a 46% decrease in g s. Leaf water loss from transpiration, during the drought period, could result in leaf water stress which would exacerbate heat effects on photosynthesis. During summer, the increase in leaf temperatures decreased g s which in turn decreased A net. Consequently, stomatal control in Quercus ilex may be considered as an adaptive strategy during drought.
doi: 10.1080/11263500012331350295
Keywords: Leaf temperature; photosynthetic activity; Quercus ilex; Stomatal conductance